Low-dose radiation employed in diagnostic imaging causes genetic effects in cultured cells - Ponzinibbio, Maria Virginia (2010)
Background: Exposure to environmental, diagnostic, and occupational sources of radiation frequently involves low doses. Although these doses have no immediately noticeable impact on human health there is great interest in their long-term biological effects. Purpose: To assess immediate and time-delayed DNA damage in two cell lines exposed to low doses of ionizing radiation by using the comet assay and micronucleus test, and to compare these two techniques in the analysis of low-dose induced genotoxicity. Material and Methods: CHO and MRC-5 cells were exposed to 50 milliSievert (mSv) of ionizing radiation and assayed immediately after irradiation and at 16 or 12 passages post-irradiation, respectively. Comet assay and micronucleus test were employed. Results: The comet assay values observed in 50 mSv-treated cells were significantly higher than in the control group for both sample times and cell lines (P < 0.001). Micronuclei frequencies were higher in treated cells than in the control group (P < 0.01, CHO cells passage 16; P < 0.05, MRC-5 cells immediately after exposure; P < 0.01 MRC-5 cells passage 12). Correlation analysis between the two techniques was statistically significant (correlation coefficient 0.82, P < 0.05 and correlation coefficient 0.86, P < 0.05 for CHO and MRC-5 cells, respectively). Cells scored at passages 12 or 16 showed more damage than those scored immediately after exposure in both cell lines (no statistically significant differences). Conclusion: Cytomolecular and cytogenetic damage was observed in cells exposed to very low doses of X-rays and their progeny. A single low dose of ionizing radiation was sufficient to induce such response, indicating that mammalian cells are exquisitely sensitive to it. Comet and micronucleus assays are sensitive enough to assess this damage, although the former seems to be more efficient.